Serum inflammatory factors such as MMP-9 are associated with post-percutaneous transluminal angioplastyacute myocardial infarction in coronary heart disease patients complicated by lower extremity arteriosclerosis obliterans: Arteriosclerosis obliterans of lower extremities with coronary heart disease - Shao, Changgang; Wuren, Batu; Chi, Guoqing; Ren, Hongcheng; Li, Fang; Song, Wenjie; Wang, Bin; Ding, Mingchao (Cellular and Molecular Biology, 2023)
This clinical study mainly analyzed the correlation of changes in serum inflammatory factors (IFs), such as matrix metalloproteinase (MMP)-9, hypersensitive C-reactive protein (hs-CRP), tumor necrosis factor (TNF)-α, and interleukin (IL)-6 with post-percutaneous transluminal angioplasty (PTA)acute myocardial infarction (AMI) in coronary heart disease (CHD)patients complicated by lower extremity arteriosclerosis obliterans (ASO). This retrospective study selected sixty ASO+CHD patients (ASO group) who underwent lower limb angioplasty between January 2014 and June 2016, as well as 50 concurrent healthy controls (HCs, HC group). According to the occurrence of AMI after PTA, cases were further subdivided into AMI (n = 18) and non-AMI (n = 42) groups. For all participants, IFs (MMP-9, hs-CRP, TNF-α, and IL-6) were detected on an empty stomach. The correlations of these IFs with the post-PTAAMI risk of ASO + CHD patients were analyzed using Pearson correlation coefficients, and their predictive value for AMI was visualized by receiver operating characteristic (ROC)curves. Finally, the prognostic factors of perioperative AMI in ASO+CHD patients were identified by multivariate analysis using the Cox model. MMP-9, hs-CRP, TNF-α and IL-6 presented statistically higher levels in the AMI group than in non-AMI and HC groups and were positively correlated with AMI. ROC analysis data showed that MMP-9, hs-CRP, TNF-α and IL-6 had better diagnostic performance, sensitivity and specificity for post-PTAAMI in patients with ASO+CHD. According to Cox multivariate analysis, high levels of MMP-9, hs-CRP and IL-6 increased the risk of perioperative AMI in ASO+CHD patients after PTA. This study shows a significant correlation between the changes of serum IFs (MMP-9, hs-CRP, IL-6, and TNF-α) and post-PTA AMI in ASO patients complicated by CHD. Patients with upregulated post-PTA levels of the above Ifs in serum are at an elevated risk of developing AMI, and active and effective control will help to prevent AMI.